Evaluation Of Regional Financial Perfomance And Trends In Local Revenue Of The City Of Bengkulu - Prasetia, Zelinda; Susanti, Neri; Astuty, Kamelia (UNIVED Press, 2026)
Regional financial management is crucial for achieving fiscal independence and improving community welfare in the era of regional autonomy. Many regional governments still face challenges in optimizing Regional Original Revenue (PAD), including Bengkulu City, which shows low effectiveness and limited fiscal independence. This study uses a quantitative descriptive method with secondary data from the Central Statistics Agency (BPS) and the Directorate General of Fiscal Balance (DJPK) for 2018–2024. Analysis focuses on PAD effectiveness, expenditure efficiency, fiscal independence, and PAD trends, with future projections calculated using the Least Square method. Results show an average PAD effectiveness of 76.60% (ineffective), expenditure efficiency of 83.53% (fairly efficient), and fiscal independence of 16.11% (very low). PAD trends show a positive trajectory, with projected revenue reaching 198.32 billion rupiah by 2029. Overall, financial performance of Bengkulu City Government is fairly good but not yet optimal. Recommendations include improving PAD management, expanding the tax base, and optimizing public spending. For further research, adding variables such as PAD’s contribution to the budget and detailed analysis of regional expenditure is suggested to provide a more comprehensive evaluation. This study contributes to understanding regional financial performance and offers insights for policy and strategic planning in local governance.